Tissue factor and thrombosis: The clot starts here - Owens, 3rd, A Phillip; Mackman, Nigel (Thrombosis and haemostasis, 2010)
Thrombosis, or complications from thrombosis, currently occupies the top three positions in the cardiovascular causes of morbidity and mortality in the developed world. There are a limited number of safe and effective drugs to prevent and treat thrombosis. Animal models of thrombosis are necessary to better understand the complex components and interactions involved in the formation of a clot. Tissue factor (TF) is required for the initiation of blood coagulation and likely plays a key role in both arterial and venous thrombosis. Understanding the role of TF in thrombosis may permit the development of new antithrombotic drugs. This review will focus on the role of TF in in vivo models of thrombosis.